PENGARUH KAPABILITAS PEMASOK TERHADAP KEPERCAYAAN DAN KINERJA OPERASIONAL PEMASOK PADA PERUSAHAAN MIKRO DAN KECIL (IMK) KABUPATEN BANTUL - , Wirdah Irawati, SE.; , Dr. Wakhid Slamet Ciptono, MPM., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study examines the influence of suppliers capability toward companyâs trust and the influence of companyâs trust on the operational performance of suppliers. The study conduct two capabilities as independent variable: operational flexibility capabilities and collaboration capabilities. Supplier's operational performance is measured through 3 criteria: quality, delivery and cost. This study uses survey method on small and micro enterprises (SMEâs) in handicraft manufacturing industries as respondent. The research methodology used Structural Equation Modelling (SEM) using Partial Least Square (PLS) software with a sample of 106 SMEâs in Bantul regency, Yogyakarta. The results show that a significant influence between capabilities flexibility and collaboration capabilities on companyâs trust. Trust also significantly influence on the operational performance of supplier.